Emočná a sociálna inteligencia adolescentov zdravotne oslabených a telesne postihnutých - Karaffová, E. (Eva); Baumgartner, F. (František) (2010)
The concept of intelligence is currently linked to different theoretical meanings, as well as conceptual ambiguity of the construct. It is shown to the importance of the analysis of the relationships of emotional intelligence in terms of the model as the personality feature and also to the abilities towards social competences which are very important in early adolescence. Understanding the concept of emotional intelligence is not uniform and there is some overlap with the concept of social intelligence. This paper deals with relationships of emotional intelligence as personality feature and social intelligence. The data were obtained in the selection of health weakened and disabled adolescents through a Trait Emotional Intelligence Questionnaire (TEIQue) and the range of the Tromso Social Intelligence Scale (TSIS).